Pancreatic abscess - Morelli Brum, Raúl; Liard, Washington; Bertullo, Hugo; Pomi, Jorge; Perdomo, Roberto (Cirugía del Uruguay, 1977)
Pancreatic abscess is a rare anatomo-clinical occurrence with a highdeath-rate, which follows necrotico-hemorrhagic and traumatic pancreatitis. Its tendency to invade may affect any of the adjacent víscera and may even involve the peritoneum. Usually there is considerable septic symptomatology. It is important to establish an early diagnosis leading to timely surgery. Furthermore, it should be distinguished from supurated pseudocysts. Two cases are discussed.